Technological innovations in major world oil crops, Volume 2 : Perspectives - Gupta, S.K (Springer New York, 2012)
The present volume presents essential information on advancements in oilseed production, processing and utilization. Advances in the technology of seed processing to produce oil and oil quality for edible and industrial applications are well presented, followed by hybrid technology, biotechnology, oil technology and meal quality for animal nutrition. The following areas are also covered: the potential for oil in developing biodiesel markets, fatty acid long chains and their derivative, pollination management, and safety of pollinators from harmful effects of pesticides. This volume also includes an economic assessment of oilseed integrated pest management (IPM) programs in different regions of the world. Dr. Surinder Kumar Gupta is Professor/Chief Scientist (Oilseeds) Plant Breeding & Genetics and Nodal officer in School of Biotechnology, S K University of Agricultural Sciences & Technology, Faculty of Agriculture, Chatha, Jammu-India. He holds a distinguished academic and service record and has been devoted primarily to research on oilseed Brassicas for nearly two decades. He has written two books on plant breeding and edited three  volumes, one on 'Recent Advances in Oilseed Brassicas', Kalyani Publishers, New Delhi, India, second on 'Rapeseed Breeding-Advances in Botanical Research', Vol. 45, Academic Press, Elsevier Publishers and third on Biology and Breeding of crucifers, CRC Publishers, Taylor and Francis Group.